Designing New Strategy for Enhancing Robusta Coffee Production: An Application of Interpretative Structural Modeling - Andi Nuddin; Reskiana Reskiana; Arman Arman; Syarifuddin Yusuf; Nuringsih Nuringsih; Muhammad Arsyad; Andi Bustan; Alimuddin Laapo (International Journal of Agriculture System, 2018)
One of the causal factors affect coffee production declining in Indonesia is the decline in harvest area of coffee plants. The decline in the area of coffee farming is caused by the shift of farmers from coffee to other commodities, such as corn, vegetables and fruit. The research was conducted to determine new strategic steps in order to enhance robusta coffee production. To achieve the research objectives, Interpretative Structural Modeling (ISM) analysis and modeling techniques are carried out. This modeling technique does not require a large sample, so the sample used in this study is limited to 22 people from several related agencies. Data processing in research is carried out according to the needs of Interpretative Structural Modeling (ISM) analysis. The results show that the new strategy in developing Robusta coffee production is (1) rehabilitation of coffee plants, (2) rejuvenation of coffee plants, (3) selection of superior coffee varieties, (4) provision of farming roads, (5) coffee price stabilization, (6) intensification of coffee plants, (7) pest control, and (8) increased knowledge of farmers. These new combinations strategy can be strongly expected to enhance robusta coffee production in the country.